2016
DOI: 10.1186/s12879-016-2069-y
|View full text |Cite
|
Sign up to set email alerts
|

Serological assessment of the establishment of herd immunity against measles in a health district in Malaysia

Abstract: BackgroundMalaysia still faces challenges optimizing resources to effectively eliminate measles through high immunization and herd immunity, with sporadic outbreaks of measles as evidence. The objective of this study is to determine the age-specific positive measles antibodies seroprevalence used for assessing the establishment of herd immunity against measles in different age groups. This is useful for identifying vulnerable age groups requiring supplementary immunization.MethodsA seroprevalence study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…In this study, while the proportion of male respondents seropositive to measles was higher than females, an analysis of differences in gender seroprevalence was not demonstrated, in line with other measles seroprevalence studies (Hazlina et al, 2016;Levine et al, 2015 This study observed that there was no significant difference in measles seroprevalence between respondents that were born in Kenya and those born outside Kenya. A review of the literature on the effect of place of birth as a predictor for positive measles antibodies is inconclusive.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, while the proportion of male respondents seropositive to measles was higher than females, an analysis of differences in gender seroprevalence was not demonstrated, in line with other measles seroprevalence studies (Hazlina et al, 2016;Levine et al, 2015 This study observed that there was no significant difference in measles seroprevalence between respondents that were born in Kenya and those born outside Kenya. A review of the literature on the effect of place of birth as a predictor for positive measles antibodies is inconclusive.…”
Section: Discussionsupporting
confidence: 88%
“…The age groups selected by the WHO correspond to preschool children (1–4 years), primary school children (5–9 years), secondary school children (10–14 years), and adults (≥15 years). Anti-measles immunity protection (or susceptibility) in different age groups can be assessed by means of developing serological surveys in representative samples of the population [ 15 , 16 ]. The WHO assumed that recommended anti-measles immunity levels were sufficient to establish the herd immunity required to block measles transmission in the community [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 2006 study focusing on primary immunization coverage in the state of Sabah noted a defaulter rate of 16.8%, with working mothers found as one of the factors associated with defauters [9]. A seroprevalence study done in Seremban district in Malaysia revealed a seropositive rate for measles to be 87% [10]. In Malaysia, based on the Ministry of Health's vaccination schedule, children aged 12 months are recommended to receive eight basic primary immunization; BCG, Hepatitis Dose 1, 2 and 3, Diphteria-Tetanus-Pertussis-Haemophilus Influenza Dose 1, 2 and 3, and Measles-Mumps -Rubella.…”
Section: Introductionmentioning
confidence: 99%